Wages, skills, and skill-biased technical change: The canonical model revisited - Audra J. Bowlus; Lance Lochner; Chris Robinson; Eda Suleymanoglu (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2021)
The canonical supplydemand model of the wage returns to skill has been extremely in uential; however, it has faced several important challenges. Several studies show that the standard approach sometimes produces theoretically wrong-signed elasticities of substitution, yields counterintuitive paths for skill-biased technical change (SBTC), and does not account for the observed deviations in college premia for younger vs. older workers. This paper shows that these failings can be explained by mis-measurement of relative skill prices and supplies (based on standard demographic composition-adjustments) and by inadequate ad hoc functional form assumptions about the path for SBTC. Improved estimates of skill prices and supplies that account for variation in skill across cohorts within narrowly defined groups help explain the observed deviation in the college premium for younger vs. older workers, even with perfect substitutability across age. Re-estimating the model with these prices and supplies produces a good fit with better out-of-sample prediction and robustly yields positive elasticities of substitution between high and low skill workers. The estimates suggest greater substitutability across skill and a more modest role for SBTC. We implement two new approaches to modelling SBTC. First, we study the extent to which recessions induce jumps or trend-adjustments in skill bias and find evidence that both features are important (but differ across recessions). Second, we link SBTC to direct measures of information technology investment expenditures and show that these measures explain the evolution of skill bias quite well. Together, these approaches suggest that the ad hoc assumptions for SBTC previously employed in the literature are too crude to fit the data well, leading to the incorrect conclusion that SBTC slowed during the early-1990s and under-estimates of the elasticity of substitution between high and low skill workers.
Keywords: 330; Qualifikation; Bildungsertrag; Lohnstruktur; Technischer Fortschritt; Schätzung; USA